Dinamika Psikologis Pengambilan Keputusan Orang Tua Menikahkan Dini Anak Akibat Hamil di Luar Nikah - Triyono, Triyono (Universitas Islam Negeri Raden Intan Lampung, 2022)
The decision to marry off children in early age due to premarital pregnancy is one of the most difficult decisions for parents. There is a psychological dynamic that accompanies the decision-making process. There is a basis and process for making these decisions. The purpose of this study is to gain an understanding of the psychological dynamics of decision making by parents who marry off their children at an early age due to premarital pregnancy. This type of research is a qualitative research with a case study approach. The subjects in this study were five parents who were selected through purposive sampling. The Data collection techniques using in-depth interviews. Data analysis uses interactive analysis by Miles and Huberman with analysis activities consisting of three flows of activities that occur simultaneously, namely data reduction, data presentation, and conclusion drawing/verification. The results show that there are psychological dynamics that accompany the decision-making process of parents in marrying children due to premarital pregnancy. The various reactions that parents show when they find out that their child is pregnant are generally in the form of negative emotion, such as: shocked, upset, anger, sadness, disappointment, disbelief, and shame. The decision making by the subject's parents considers some basic decision making in the form of intuition, rationale, facts, experience and authority. There are four decision-making processes, namely: intelligence, design, choice, and implementation. According to the subject, the decision to marry off the children is the best alternative in solving the problem of premarital pregnancy.Keywords: Psychological Dynamic, Decision Making, Early Marriage, Premarital Pregnancy